The tracking of internal and external training loads with next-day player-reported fatigue at different times of the season in elite soccer players - Draper, G.; Wright, M.; Chesterton, P.; Atkinson, G. (International Journal of Sports Science & Coaching, 2021)
The aim was to assess factor structure of player-reported fatigue and quantify within-subjects association between changes in training load measures and next day player-reported fatigue at different time points of an elite football season. Using longitudinal research design, twenty-four professional footballers, mean (SD) age of 25.7 (3.4) years, were monitored during their competitive season, including pre-season. Player-reported fatigue data and session ratings of perceived exertion (session-RPE) were collected via a mobile application. Player`s Heart rate (HR) and global positioning system (GPS) data were collected daily for each player in field sessions. Principal component analysis (PCA) indicated three components with Eigenvalues above 1.0; "soreness", "mood, and "hydration". Within-player correlations between training load values and next day player-reported fatigue values were trivial to moderate (r ˜ -0.42 to -0.04). In-season we observed large correlations between Total Distance (TD) and PlayerLoad with Soreness (r = -0.55, 95% CI: -0.62 to -0.46; r = -.054, 95% CI: -0.62 to -0.46), but during pre-season, correlations were small (r = -0.15, 95% CI: -0.28 to -0.01; r = -0.13, 95% CI: -0.26 to 0.01). The HR TRIMP, TD and session-RPE measures each showed trivial to moderate correlations (r ˜ -0.41 to -0.08) with next day "mood". Our in-house player-reported fatigue questionnaire was sensitive to the multi-dimensional nature of fatigue, identifying physiological (soreness), psychological (mood and stress) and nutritional (hydration and nutrition) components. We found the in-season correlations with training load to be greater than previously reported in the literature, specifically with next day player-reported "soreness". Nevertheless, the correlations between the items of our scale and pre-season training load were small.